The Effects of Dolomitic Limestone and Gypsum on Chemical Properties of an Ultisol and Oxisol in Malaysia and on the Growth of Corn (Zea Mays L.) - Hashim, Ismail (1992)
Ultisols and Oxisols are acidic in nature, with low CEC, low exchangeable bases, and high Al saturation, and are dominated by variable-charged minerals. The soils need to be ameliorated before they can be utilized productively. This study was conducted to determine the react ions taking place in the soils as affected by limestone and gypsum applications and to assess the effects of these changes on the growth of corn. Based on mineralogy, charge and texture, two soils were selected for investigation in the glasshouse. These soils were Bungor (Ultisol) and Prang series (Oxisol). In experiment, the soils were repacked into PVC leaching columns to a depth of 90cm. Ground magnesium limestone (GML), gypsum and their combinations were incorporated into the soils at 0-5 cm depth, and were subjected to leaching environments for 6 months. In experiment 2, the soils were mixed with GML, gypsum and their combinations as a precursor to a glasshouse trial to asses the response of corn to the ameliorants.